Urban Segregation Even on Holiday: Income Differences in the Choice of Destinations - Ana Condeço-Melhorado; Juan Carlos García-Palomares; Javier Gutiérrez (Findings)
Urban income segregation manifests in tourist destination choices. We analyze the relationship between residential income levels and travel patterns from Madrid to the Spanish coastal destinations of Marbella and Torremolinos using mobile phone data from August 2021. By employing spatial analysis techniques such as location quotient (LQ) and Theil index, we assess the degree of specialization of Madrid’s neighborhoods in these destinations. Results show a clear income differentiation: high-income residents exhibit a strong preference for Marbella, while Torremolinos attracts a more socially diverse visitor profile. These findings highlight the influence of urban socio-spatial dynamics on tourism mobility and suggest that economic segregation shapes leisure travel choices.